A comparative observational study of fetomaternal outcome in gestational hypertension cases in coronavirus disease 2019 versus noncoronavirus disease 2019 patients - Sangeeta Shah; Rajala Usha Rani; P. Divya Daniel; C. H. Udaya Sri (MRIMS Journal of Health Sciences)
Background Coronavirus disease 2019 (COVID-19) which primarily involves the pulmonary system can also cause systemic involvement by panvascular endothelial dysfunction. Gestational hypertension is a systemic disease of maternal endothelial dysfunction which can progress to preeclampsia, eclampsia, and multi-organ failure. Both the entities: COVID-19 and preeclampsia appeared to have camouflaged scenarios ultimately, presenting as endothelial dysfunction. Objective The present study aimed to estimate the number of COVID-19 and non-COVID-19 patients with gestational hypertension developing preeclampsia and their fetomaternal outcome in the third trimester. Materials and Methods It was a comparative observational study conducted in the Department of Obstetrics and Gynecology at Gandhi Hospital, Secunderabad, over a period of 18 months during the COVID-19 pandemic. One hundred women diagnosed with gestational hypertension were considered and their maternal and fetal complications were studied. They were divided into two groups based on the history of symptomatic COVID-19 infection and the COVID-19 reverse transcription–polymerase chain reaction (RT-PCR) report. Results The incidence of severe preeclampsia was more in the gestational hypertension with COVID-19 group (60%) when compared to the non-COVID-19 group (36%) (P = 0.016). The incidence of maternal deaths in the gestational hypertension with COVID-19 group was 20% (P = 0.08). Incidence of intrauterine growth restriction was 20% (P = 0.205) and neonatal deaths was 14% (P = 0.538) in the gestational hypertension with COVID-19 group. Conclusion Preeclampsia and COVID-19 infection during pregnancy were closely related with each other. In a synergistic fashion, COVID-19 infection with preeclampsia increases the risk of adverse maternal and perinatal outcomes.